Price-Denomination Effect: Choosing to Pay With Denominations That Are the Same as the Product Prices - Reutskaja, Elena; Iyamabo, Jeremiah; Raghubir, Priya; Gallo, Iñigo (Frontiers in Psychology, 2020)
Building on past research on judgment anchoring, we investigate the effect of price information on consumers’ choice of denomination when making a purchase. Across seven experiments, including two in the field (N = 4,020), we find that people tend to purchase with denominations that are the same as the product prices. They use larger denominations for higher priced products that are priced at the value of the denomination held, and smaller denominations for lower priced products that are priced at the value of the smaller denomination held. The effect is not explained by storage or purchase convenience. We propose the “price-denomination effect” is driven by consumers anchoring on product price and then choosing the denomination that matches the anchor. The effect replicates across participants from different continents (U.S, Europe, and Africa) and samples (online panelists, and actual consumers), as well as prices in different currencies (US $, €, and Nigerian Naira). We further demonstrate that people´s preference for denominations also affects the choice of the form of payment used: cash versus card. Consumers are more likely to use cash (vs. card) when product price is exactly the same as a denomination held. We conclude with a discussion of theoretical and practical implications.